2018
DOI: 10.1111/jfpp.13623
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cantonese sausage fermented by a mixed starter culture

Abstract: L. plantarum, P. pentosaceus, and D. hansenii isolated from Cantonese sausage were investigated for their potential as a mixed starter culture with the capability to improve sausage quality. Results unveiled that Cantonese sausage produced with the mixed starter culture exhibited low nitrite residue and low‐fat content advantages over fermented sausage without starter culture. Different fermentation time possessed different influence on physicochemical parameters, free amino acids (FAAs) composition and textur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…It is stipulated that the nitrite amount in the final meat products must be controlled below 20 mg/kg (Huang et al 2011). In this study, the finding indicates that starter culture inoculation contributed to nitrite depletion and safety improvement of Cantonese sausages, which is in agreement with those reported by Cheng (Cheng et al 2018).…”
Section: Effect Of the Starter Culture On Nitrite Depletion And Histamine Accumulation In Cantonese Sausagessupporting
confidence: 92%
“…It is stipulated that the nitrite amount in the final meat products must be controlled below 20 mg/kg (Huang et al 2011). In this study, the finding indicates that starter culture inoculation contributed to nitrite depletion and safety improvement of Cantonese sausages, which is in agreement with those reported by Cheng (Cheng et al 2018).…”
Section: Effect Of the Starter Culture On Nitrite Depletion And Histamine Accumulation In Cantonese Sausagessupporting
confidence: 92%
“…From the results, we can also observe that the concentrations of aspartic acid (Asp), glutamic acid (Glu), alanine (Ala), isoleucine (Ile) and phenylalanine (Phe) in EG were higher than that in CG. Glu greatly promoted the formation of the umami taste of fermented sausages and Ala and Asp help impart a sweet taste (Cheng et al ., 2018). An increase in the contents of valine (Val) and proline (Pro) was also observed in EG.…”
Section: Resultsmentioning
confidence: 99%
“…Both strains proved to reduce pH of sausage during processing, which depleted the residual nitrite content and also increase the microbiological safety. Likewise, Cheng et al [90] obtained a 43% reduction of residual nitrite content due to the inoculation of Lactiplantibacillus plantarum GIM 1.191, Pediococcus pentosaceus GIM 1.428, and Debaryomyces hansenii GIM 2.184 in the production of Chinese Cantonese sausage. Wang et al [91] reported a similar effect in the production of Chinese Cantonese sausage with a multi-species starter culture (Lactobacillus sakei, Pediococcus pentosaceus, Staphylococcus xylosus, and Staphylococcus carnosus) in relation to non-inoculated sausage.…”
Section: Residual Nitrite and Nitrosamine Accumulation And Microbial ...mentioning
confidence: 94%